2016
DOI: 10.7150/thno.14145
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Visualization of Tumor Antigen-containing Microparticles Generated in Fluorescent-protein-elicited Immunity

Abstract: In vivo optical spatio-temporal imaging of the tumor microenvironment is useful to explain how tumor immunotherapies work. However, the lack of fluorescent antigens with strong immunogenicity makes it difficult to study the dynamics of how tumors are eliminated by any given immune response. Here, we develop an effective fluorescent model antigen based on the tetrameric far-red fluorescent protein KatushkaS158A (tfRFP), which elicits both humoral and cellular immunity. We use this fluorescent antigen to visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The presence of T-MPs in tumor microenvironments is a general pathophysiological phenomenon (40). Such continuously produced T-MPs in the interstitial fluid of extracellular space may enter lymph or papillary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of T-MPs in tumor microenvironments is a general pathophysiological phenomenon (40). Such continuously produced T-MPs in the interstitial fluid of extracellular space may enter lymph or papillary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the combined system outperformed the single system, and it was suitable for quantitative three‐dimensional imaging of the fluophor . Furthermore, aiming at the significant demand for the visualization research of tumor immunity, they developed multiscale optical imaging approaches , optimized red‐shift fluorescent protein probes , established multicolor labeling animal models, and achieved the in vivo visualization of specific antitumor immune response and immunotherapy .…”
Section: Selected Research Achievementsmentioning
confidence: 99%
“…Further, we assessed the ability of α-melittin-NPs to induce the apoptosis and necrosis of tumor cells and the release of endogenous tumor antigens in vivo. tfRFP-B16F10 tumor cells that expressed tetrameric far-red fluorescent protein (tfRFP) were used to visualize the release of endogenous antigens 32 . The fluorescence imaging of tumor tissue sections showed that both melittin and α-melittin-NPs induced the disappearance of fluorescent model antigens in the tumor section after 24 h, indicating the changes in membrane penetrability and the release of the tumor antigens ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%